School autonomy and 21st century skills in the Israeli educational system: Discrepancies between the declarative and operational levels. Issue 7 (12th September 2016) - Nir, Adam; Ben-David, Adi; Bogler, Ronit; Inbar, Dan; Zohar, Anat
Abstract : Purpose: The following article analyzes two parallel processes in the Israeli educational system: first, the idea of school autonomy, exploring its origins and its pedagogical implications and effectiveness, and second, the development of the progressive education evident mainly in the cognitive domain of 21st century skills, focusing on fostering "deep knowledge" and children's thinking skills. The manuscript explores the various "waves" of progressive pedagogies that have taken place in the Israeli school system over the years, describing and analyzing the processes that characterize them. Design/methodology/approach: Based on a historical perspective, the paper describes chronologically the main developments related to school autonomy and 21st century skills policy initiatives, based on a literature review and analysis of policy documents. Findings: The review indicates that the Israeli educational system is still caught in the "centralization trap, " inhibiting major changes in the patterns of central control and degrees of freedom granted to school level educators. As for school pedagogy, it is evident that most of the changes in pedagogy suggested by the numerous policy documents over the years have not resulted in sustainable, system-wide change. In both issues a large disparity is evident between declarations about innovative pedagogies and school autonomy and their actual implementation. Originality/value: Our review reflects the idiosyncratic articulation of policy plans conducted by the Ministry of Education, producing discrepancies and incongruences at the school level. Some implications of the "declarative culture" created are further discussed.